Fabrication and characterization of agarwood extract-loaded nanocapsules and evaluation of their toxicity and anti-inflammatory activity on RAW 264.7 cells and in zebrafish embryos - Eissa Manar (Tanjung Malim, 2021)
Fabrication and characterization of agarwood extract-loaded nanocapsules and evaluation of their toxicity and anti-inflammatory activity on RAW 264.7 cells and in zebrafish embryos by Eissa Manar